Technical barriers and development of Cu wirebonding in nanoelectronics device packaging - C., L. Gan; E., K. Ng; B., L. Chan; Uda, Hashim, Prof. Dr.; F., C. Classe (Hindawi Publishing Corporation, 2013)
Link to publisher's homepage at http://www.hindawi.com